2011
DOI: 10.1242/dev.057331
|View full text |Cite
|
Sign up to set email alerts
|

Brassinosteroids control meristem size by promoting cell cycle progression in Arabidopsis roots

Abstract: SUMMARYBrassinosteroids (BRs) play crucial roles in plant growth and development. Previous studies have shown that BRs promote cell elongation in vegetative organs in several plant species, but their contribution to meristem homeostasis remains unexplored. Our analyses report that both loss-and gain-of-function BR-related mutants in Arabidopsis thaliana have reduced meristem size, indicating that balanced BR signalling is needed for the optimal root growth. In the BR-insensitive bri1-116 mutant, the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

42
417
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 456 publications
(473 citation statements)
references
References 70 publications
(104 reference statements)
42
417
0
3
Order By: Relevance
“…This observation is in accordance with many studies where similar criteria to determine the RAM/EZ boundary have been used, and which report meristem length increase beyond 5 d after germination (DAG) and later (Galinha et al, 2007;Ubeda-Tomas et al, 2009;Gonzalez-Garcıa et al, 2011;Makkena and Lamb, 2013). Moreover, a kinematic analysis of the arabidopsis root showed that accelerated root growth is mainly due to an increased cell production rate during the first 14 DAG and a steady increase in meristem length during the first 2 weeks of growth after germination (Beemster and Baskin, 1998).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This observation is in accordance with many studies where similar criteria to determine the RAM/EZ boundary have been used, and which report meristem length increase beyond 5 d after germination (DAG) and later (Galinha et al, 2007;Ubeda-Tomas et al, 2009;Gonzalez-Garcıa et al, 2011;Makkena and Lamb, 2013). Moreover, a kinematic analysis of the arabidopsis root showed that accelerated root growth is mainly due to an increased cell production rate during the first 14 DAG and a steady increase in meristem length during the first 2 weeks of growth after germination (Beemster and Baskin, 1998).…”
Section: Discussionsupporting
confidence: 91%
“…Although useful for rough qualitative evaluations, without measuring cell lengths the identification of the point where rapid elongation starts may vary among researchers. A relatively more objective way of determining this boundary implies finding the position at which cell length in a file is more than twice that of the previous cell (Gonzalez-Garcıa et al, 2011). The latter method may yield biased results: before rapid elongation starts, a longer cell can be followed by a shorter cell in the TD, indicating that this criterion is not always sufficient for objective establishment of the RAM/EZ boundary.…”
Section: Introductionmentioning
confidence: 99%
“…Our genetic studies revealed that BES1 regulates the differentiation of procambial cells into xylem cells. Similarly, a previous study has demonstrated that BES1 is involved in the differentiation of columella stem cells 49 , suggesting a common role of BES1 in the regulation of stem cell differentiation.…”
Section: Discussionsupporting
confidence: 65%
“…This may not be so uncommon in hormone effects, as, for instance, a study on the role of an ethylene-responsive factor in flg22-mediated growth inhibition revealed that both mutation and overexpression had the same effect, leading to the conclusion that it is maintained at an optimal level and that any deviation tips the fragile signaling balance (Bethke et al, 2009). Similarly, root meristem size is regulated by a fine balance of brassinosteroid signaling, and modulation of this pathway in either direction leads to short-root phenotypes ( González-García et al, 2011). It is also interesting that perturbations of DELLA levels sufficient to disturb the stress-induced cell differentiation generally do not affect ploidy levels under normal conditions.…”
Section: Discussion Dellas Control Mitotic Exit Induced By Osmotic Stmentioning
confidence: 99%